Acute respiratory failure as primary manifestation of antineutrophil cytoplasmic antibodies-associated vasculitis - Evdokia Sourla; Vasilis Bagalas; Helias Tsioulis; Asimina Paspala; Sofia Akritidou; Athanasia Pataka; Katalin Fekete; Ioannis Kioumis; Ioannis Stanopoulos; Georgia Pitsiou (Clinics and Practice, 2014)
The systemic vasculitides are multifocal diseases characterized by the presence of blood vessel inflammation in multiple organ systems. Their clinical presentation is variable extending from self-limited illness to critical complications including diffuse alveolar hemorrhage and glomerulonephritis. Alveolar hemorrhage is a lifethreatening manifestation of pulmonary vasculitis that can rapidly progress into acute respiratory failure requiring ventilatory support. We present the case of a 74-year-old patient admitted to the Intensive Care Unit with severe hypoxic respiratory failure and diffuse alveolar infiltrates in chest imaging that was later diagnosed as antineutrophil cytoplasmic antibodies-associated vasculitis. The report highlights the importance of differentiate between alveolar hemorrhage and acute respiratory distress syndrome of other etiology because alveolar hemorrhage is reversible with prompt initiation of treatment.